Kepemimpinan Pembelajaran Berdiferensiasi Melalui Mini Workshop Berbasis Produk Beriman (Produktif Memberi Manfaat) di SMP Negeri 3 Pagedongan - Asri Ratna Sari (UM Purwokerto Press, 2023)
The research aims to realize differentiated teaching student leadership at SMP Negeri 3 Pagedongan through mini workshops based on faith products (productive and beneficial). The implementation of activities starts in August 2022 to October 2022 at SMP Negeri 3 Pagedongan. Best experience procedures start with planning, implementation and follow-up plans. The planning stage begins with the identification of learning problems based on educational reports and initial assessments of teachers. Next identify real challenges. Implementation is carried out activities in the learning community, by carrying out learning planning and assessment activities. Then supervise the implementation of learning and reflection. The follow-up plan is used as a first step to improve the next activity. Data sources and data collection tools are the 2021 education report cards, students, teachers and the school environment. Data from students are in the form of initial assessment results and reflection results. While the data from the teacher is the result of periodic reflection. Data triangulation was carried out with documentation and testimonies from school residents and surrounding schools. Data from the school is an observation based on the implementation of differentiated learning at SMP Negeri 3 Pagedongan. The results of this study are the implementation of differentiated learning and increasing teacher competence in making good practices. The best result of this experience is an increase in the number of teachers who carry out differentiated learning in the second observation, the total score is 30 from the initial score of 8. Differentiated learning has been carried out, and the results of the differentiation of content, processes and products have been carried out. The conclusion from this best experience is that leadership in differentiated learning through mini workshops based on faith products is able to realize differentiated learning at SMP Negeri 3 Pagedongan in 2022.